Pemanfaatan Limbah Organik Menjadi Eco Enzyme Dan Kandungan Unsur Hara Makro Untuk Meningkatkan Kualitas Lingkungan - Helfa Septinar; Putri Anggraini; Eva Suryani; Rita Puspasari (Universitas PGRI Palembang, 2024)
Organic waste is waste that comes from plants and creatures; if not managed properly, it will produce methane gas, which can damage life on earth. One type of organic waste is fruit peel waste. The aim of this research is to recycle organic fruit peel waste into eco-enzymes and test the levels of eco-enzyme macro nutrients. The method used is laboratory testing with spectrophotometric and absorbance tests. The research results were pH 3.5, N 526 mg/l, P 4.2 mg/l and K 2,900 mg/l.